Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18041685
|View full text |Cite
|
Sign up to set email alerts
|

Association between Household Crowding and Violent Discipline and Neglect of Children: Analysis of Multiple Indicator Cluster Surveys in 26 Low- and Middle-Income Countries

Abstract: The influence of household crowding on physical and mental health has been well documented. However, research on the influence of household crowding on violent discipline and neglect of children is scarce. Therefore, we aimed to investigate whether household crowding was associated with violent discipline and neglect of children in low- and- middle-income countries (LMICs). Cross-sectional data for 280,005 and 73,030 children in 26 LMICs surveyed using the Multiple Indicator Cluster Survey were analyzed for (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Inadequate living conditions have also been associated with depression and stress [ 7 ], which in turn may contribute to the occurrence of violence [ 8 ]. Indeed, associations of inadequate living conditions and/or its characteristics with multiple forms of violence have been documented, such as non-partner violence [ 9 , 10 , 11 ], homicide [ 12 ], and child abuse [ 13 ]. Thus, inadequate living conditions might also be linked to IPV toward women.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate living conditions have also been associated with depression and stress [ 7 ], which in turn may contribute to the occurrence of violence [ 8 ]. Indeed, associations of inadequate living conditions and/or its characteristics with multiple forms of violence have been documented, such as non-partner violence [ 9 , 10 , 11 ], homicide [ 12 ], and child abuse [ 13 ]. Thus, inadequate living conditions might also be linked to IPV toward women.…”
Section: Introductionmentioning
confidence: 99%
“…One barrier to understanding co-occurrence in LMICs is that most high quality, national data on violent discipline come from UNICEF-supported Multiple Indicator Cluster Surveys (MICS) [28], which do not usually measure IPV prevalence. As a result, the growing number of multi-country analyses of MICS data have not included child exposure to IPV as a potential risk factor in research on violent discipline [29][30][31][32][33][34][35][36]. Conversely, most national surveys that measure IPV against women do not measure child discipline, with some exceptions, including the surveys in this study.…”
Section: Open Accessmentioning
confidence: 98%
“…A study found the relationship between violence and overcrowding population was higher in urban and poor areas. Household crowding is also related to domestic violence between adults (22), as we know that living with extended family in a house is commonplace in Indonesia. Another study on DV in Manado city in 2018-2019 linked the relationship between population density and economic factors with the incidence of DV (23).…”
Section: History Of Domestic Violencementioning
confidence: 99%